The first record of the genus Desertoniscus Verhoeff, 1930 (Isopoda, Oniscidea, Agnaridae) from Europe, with the description of a new species - Gongalsky, Konstantin B. (Zootaxa, 2017)
A new woodlouse species, Desertoniscus zaitsevi sp. nov., is described from Kalmykia, Cis-Caspian region of Russia. The diagnostic features of the new species, as well as its affinities within the genus are provided and discussed. The new species is the northwesternmost in Eurasia, expanding the known distribution of this genus into Europe.